1987
DOI: 10.1093/jac/20.suppl_b.131
|View full text |Cite
|
Sign up to set email alerts
|

Influence of amoxycillin, erythromycin and roxithromycin on colonization resistance and on appearance of secondary colonization in healthy volunteers

Abstract: We investigated the influence of oral administration of amoxycillin, erythromycin and roxithromycin on colonization resistance in healthy volunteers. Antibiotics were administered in a randomized cross-over design. No effect on the colonization resistance of the oropharynx could be demonstrated. Amoxycillin decreased the colonization resistance of the bowel against Enterobacteriaceae and yeasts, whose median concentration in faeces increased 100-fold and 30-fold respectively. Roxithromycin and erythromycin dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

1989
1989
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…Knowledge of the antibiotic impact on the fecal flora is especially helpful in neutropenic and intensive care unit patients, for whom the concept of colonization resistance (12,26,40,41) has become a major issue. In addition, the detection of resistant bacterial strains in fecal flora during or after antibiotic treatment is of great importance.…”
Section: Resultsmentioning
confidence: 99%
“…Knowledge of the antibiotic impact on the fecal flora is especially helpful in neutropenic and intensive care unit patients, for whom the concept of colonization resistance (12,26,40,41) has become a major issue. In addition, the detection of resistant bacterial strains in fecal flora during or after antibiotic treatment is of great importance.…”
Section: Resultsmentioning
confidence: 99%
“…More than 50 years ago, it was found that loss of obligate anaerobic bacterial populations from the lower gastrointestinal tract strongly correlated with susceptibility to infection, which suggests that these commensal organisms were providing colonization resistance (13). Compositional analyses of colonic microbial populations in humans after antibiotic treatment demonstrated that loss of obligate anaerobes frequently results in expansion of γ-proteobacteria and enterococci; these findings suggest that the complex, pre-antibiotic commensal microbiota suppresses the expansion of the oxygen-tolerant bacterial species (14, 15). …”
Section: Colonization Resistance Mediated By Commensal Bacteriamentioning
confidence: 96%
“…The observation that antibiotic therapy reduced colonization resistance making the host susceptible to bacterial infections was observed very early in the literature [56][57][58][59]. Gut microbial compositional analysis of an antibiotic-treated mice showed the expansion of γ-proteobacteria and enterococci, suggesting that gut microbiota somehow suppressed the expansion of oxygen-tolerant species [94,95]. A study on healthy volunteers treated for a week or less with antibiotics reported persistent effects on their bacterial flora that included a loss of biodiversity on the gut flora, insurgence of antibiotic resistance strains, and upregulation of antibiotic resistance genes [96].…”
Section: Antibiotic-associated Colitismentioning
confidence: 99%